1999
DOI: 10.1056/nejm199912233412601
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angioplasty with or without Stent Implantation for Acute Myocardial Infarction

Abstract: In patients with acute myocardial infarction, routine implantation of a stent has clinical benefits beyond those of primary coronary angioplasty alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
303
9
19

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 853 publications
(347 citation statements)
references
References 23 publications
16
303
9
19
Order By: Relevance
“…Stenting in AMI has been associated with less slow-flow, better ST segment resolution and improved procedural and clinical outcomes [1,2,3]. Therefore, we performed stenting to all our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stenting in AMI has been associated with less slow-flow, better ST segment resolution and improved procedural and clinical outcomes [1,2,3]. Therefore, we performed stenting to all our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing primary angioplasty with primary stenting for acute myocardial infarction (AMI) have shown that primary stenting improved the procedural success rate and clinical outcome [1,2,3]. GpIIb/IIIa inhibitors combined with primary stenting have improved both epicardial [4] and microvascular flow [5] and led to a greater extent of myocardial salvage in patients with AMI [6].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular complications and the need for blood transfusions occur more frequently in women, even when weight-adjusted antithrombin agents are used, 229,230 and female sex remains an independent predictor of bleeding. 231 Although early-generation stenting was associated with higher mortality in women, 232 later studies found that bare metal stenting during primary PCI compared with angioplasty in women reduced MACE rates and target vessel revascularization, without influencing death or reinfarction rates. 229 A patient-level pooled analysis comparing stent choice in women found that newer-generation drug eluting stents (DES) were associated with reduced death or MI and reduced target vessel revascularization compared with both early-generation DES and bare metal stents; however, these data were not exclusively from STEMI patients.…”
Section: Primary Pcimentioning
confidence: 99%
“…One is the chronic phase, with significant stenosis in a coronary artery and clinically stable or unstable angina, and the other is the case of acute occlusion of a coronary artery with threatening or manifest myocardial infarction. These situations are often investigated by and treated with coronary angiography followed by various interventional procedures (1,3,4).…”
mentioning
confidence: 99%